Effect of SR121566A, a Potent GP IIb-IIIa Antagonist, on the HIT Serum/heparin-Induced Platelet Mediated Activation of Human Endothelial Cells - Herbert, Jean-Marc; Savi, Pierre; Jeske, Walter P.; Walenga, Jeanine M. (Thrombosis and Haemostasis, 1998)
Heparin-induced thrombocytopenia (HIT) is a common adverse effect of heparin therapy that carries a risk of serious thrombotic events. This condition is caused by platelet aggregation, which is mediated by anti-heparin/platelet factor 4 antibodies. Sera from patients with HIT in the presence of platelets, induced the expression of E-selectin, VCAM, ICAM-1 and tissue factor and the release of IL1β, IL6, TNFα and PAI-1 by human umbilical vein endothelial cells (HUVECs) in vitro and initiated platelet adhesion to activated HUVECs. These effects which occurred in a time-dependent manner were significant in the first 1-2 h of incubation and reached a maximum after 6 to 9 h. The GP IIb-IIIa receptor antagonist SR121566A which has been shown to block platelet aggregation induced by a wide variety of agonists including HIT serum/heparin, reduced in a dose-dependent manner the HIT serum/heparin-induced, platelet mediated expression and release of the above mentioned proteins. The IC50 for inhibition of HIT serum/ heparin-induced platelet dependent HUVEC activation by SR121566A was approximately 10-20 nM. ADP, but not serotonin release, also appeared to be involved as apyrase and ATPγS blocked platelet-dependent, HIT serum/heparin-induced cell surface protein expression and cytokine release by HUVECs. Increased platelet adherence to HIT serum/heparin-activated HUVECs was inhibited by SR121566A and, to a lesser extent, by apyrase and ATPγS, showing that platelet activation and release was at the origin of the HIT serum/heparin-induced expression of these proteins by HUVECs.Thus, sera from patients with HIT induced the expression of adhesive and coagulation proteins and the release of cytokines by HUVECs through the activation of platelets which occurred in a GP IIb-IIIa-dependent manner, a process that could be selectively blocked by SR121566A.